Microendoscopic Lumbar Posterior Decompression Surgery for Lumbar Spinal Stenosis: Literature Review - Akinobu Suzuki; Hiroaki Nakamura (Medicina, 2022)
Lumbar spinal stenosis (LSS) is a common disease in the elderly, mostly due to degenerative changes in the lumbar spinal complex. Decompression surgery is the standard surgical treatment for LSS. Classically, total laminectomy—which involves resection of the spinous process, entire laminae and medial facet—has been the standard decompression technique; however, it can cause post-surgical instability. To overcome this disadvantage, various minimally invasive techniques that preserve the stabilization structures of the spine have been developed, and surgeons have begun to re-evaluate decompression surgery from the standpoint of reduced invasiveness and cost. More than two decades have passed since the introduction of microendoscopic spine surgery, and studies continue to shed light on its advantages and limitations as new knowledge becomes available. This article is a narrative review of the available literature, along with authors’ experience, regarding the indications, surgical techniques, clinical outcomes, and limitations/complications of microendoscopic decompression for LSS.